Energy requirements for dairy calves. - Elizondo-Salazar, Jorge Alberto (Agronomía Mesoamericana, 2013)
The objective of this work was to present the daily energy requirements of dairy heifer calves extracted from the National Research Council (2001) publication: Nutrient Requirements of Dairy Cattle, during the year 2012 at the Alfredo Volio Mata Experiment Station with the purpose of making this information more available to potential users in Costa Rica and Latin America. The calf requires special care and attention in order to survive from birth to weaning and beyond. From a nutritional point of view, establishing the energy require-ments of the young calf could help producers provide diets in order to meet nutrients demands for optimum growth and good health.